THE IMPACT OF BODY MAPPING ON BODY PART RECOGNITION IN FOURTH-GRADE STUDENTS WITH HEARING LOSS - Khalishah Nawwar Ariesta Putri; Erma Kumala Sari; Tias Martika (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
Students with hearing loss are included among children with special needs. Students with hearing loss are people with mild to severe hearing impairments. This study aims to determine the effect of body mapping media on the ability to recognize body parts in fourth-grade students with hearing loss at SLB YRTRW Surakarta in the 2024/2025 academic year. This study is a quantitative pre-experimental study with a one-group pretest-posttest research design. This data collection technique uses an action test obtained through observation. The validity technique in this study uses content validity which is calculated using Aiken's V formula. The reliability test in this study uses interrater reliability using the ICC calculation. The data that has been collected was analyzed using a non-parametric test in the form of the Wilcoxon Sign Rank Test. The results of this study include the results of the assessment of the action test of the ability to recognize body parts of fourth-grade students with hearing loss. The average pretest score was 54.92, while the posttest score was 82.12. This study concludes that body mapping media affects the ability to recognize body parts in fourth-grade students with hearing loss at SLB YRTRW Surakarta in the 2024/2025 academic year.